Sistem Informasi Penjualan Batu AKIK Berbasis Web - Suminten, Suminten; Rani, Rani; Amri, Amri (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2019)
The stone that many people today know is Agate, agate has its own uniqueness and privileges, so many agates that many people want to have. Agate which is now commonly found by the wider community, it affects the desire of agate traders to increase their sales turnover. The main problem faced by sellers is that the system used is still manual, such as making reports, there are often errors in the sum of prices and stones sold, so the number of stones sold at the total price often does not match the actual results. With these main problems, a web-based sales application will be built using the waterfall model software development method with stages of analysis, design, coding and testing and data collection methods that include observation and study of literature. The application that will be built consists of a flow system that includes managing goods orders, stock items, payments, delivery of goods and sales reports. It is expected that with this system the operational activities of agate sales can be more effective and efficient so that it is expected to provide more financial benefits for business owners and facilitate customers in making purchases online without coming directly to the store.